Chloride intracellular channel protein 2 in cancer and non-cancer human tissues: relationship with tight junctions. Issue 1 (2nd January 2019) - Ueno, Yoshitomo; Ozaki, Saya; Umakoshi, Akihiro; Yano, Hajime; Choudhury, Mohammed E.; Abe, Naoki; Sumida, Yutaro; Kuwabara, Jun; Uchida, Rina; Islam, Afsana; Ogawa, Kohei; Ishimaru, Kei; et al.
ABSTRACT: Chloride intracellular channel protein 2 (CLIC2) belongs to the CLIC family of conserved metazoan proteins. Although CLICs have been identified as chloride channels, they are currently considered multifunctional proteins. CLIC2 is the least studied family member. We investigated CLIC2 expression and localization in human hepatocellular carcinoma, metastatic colorectal cancer in the liver, and colorectal cancer. Significant expression of mRNAs encoding CLIC1, 2, 4, and 5 were found in the human tissues, but only CLIC2 was predominantly expressed in non-cancer tissues surrounding cancer masses. Fibrotic or dysfunctional (aspartate aminotransferase ≥40) non-cancer liver tissues and advanced stage HCC tissues expressed low levels of CLIC2. Endothelial cells lining blood vessels but not lymphatic vessels in non-cancer tissues expressed CLIC2 as well as high levels of the tight junction proteins claudins 1 and 5, occludin, and ZO-1. Most endothelial cells in blood vessels in cancer tissues had very low expressions of CLIC2 and tight junction proteins. CD31 + /CD45 − endothelial cells isolated from non-cancer tissues expressed mRNAs encoding CLIC2, claudin 1, occludin and ZO-1, while similar cell fractions from cancer tissues had very low expressions of these molecules. Knockdown of CLIC2 expression in human umbilical vein endothelial cells (HUVECs) allowed human cancer cells to transmigrate through a HUVEC monolayer. These results suggest that CLIC2 may be involved in the formation and/or maintenance of tight junctions and that cancer tissue vasculature lacks CLIC2 and tight junctions, which allows the intravasation of cancer cells necessary for hematogenous metastasis.